Silage maize as a potent candidate for sustainable animal husbandry development—perspectives and strategies for genetic enhancement - Karnatam, Krishna Sai; Mythri, Bikkasani; Un Nisa, Wajhat; Sharma, Heena; Meena, Tarun Kumar; Rana, Prabhat; Vikal, Yogesh; Gowda, M.; Dhillon, Baldev Singh; Sandhu, Surinder (Frontiers in Genetics, 2023)
Owing to its quick growth, high biomass, good palatability and absence of any anti-nutritional components, maize is one of the most nutritious non-legume green fodders. It is a high-energy, low-protein forage commonly used for dairy animals like cows and buffalos, often in combination with a complementary high-protein forage such as alfalfa. Maize is also preferred for silage making over other fodders due to its softness, high starch content and sufficient amount of soluble sugars required for proper ensiling. With a rapid population increase in developing countries like China and India, there is an upsurge in meat consumption and hence the requirement to feed livestock with animal feeds which entail high usage of cereals and maize offers fitted candidature. The global maize silage market is projected to grow at a compound annual growth rate of 7.84% from 2021-2030. Factors such as increasing demand for sustainable and environment-friendly food sources coupled with rising health awareness are fuelling this growth. With the dairy sector growing at about 4 - 5 % and the increasing shortage faced for fodder, demand for silage maize is expected to grow worldwide. Progress in improved mechanization for provision of silage maize, less demand for labour, no moisture-related marketing issues as associated with grain maize, early vacancy of farms for next crop, easy and economical form of feed to sustain household dairy sector, are making maize silage a profitable venture. But to sustain the profitability of this enterprise, there is a need to develop hybrids specific for silage production. Diminutive focus is laid on breeding for plant ideotype for silage which has specific trait consideration viz., dry matter yield, yield of nutrients, energy in organic matter, genetic architecture of cell wall components determining their digestibility, stalk standability, and maturity span losses during ensiling etc. In this review, we have tried to explore the information on genetic basis of forage yield and quality traits and gene/gene families impacting silage yield and quality. Based on available genetic information on inheritance and molecular aspects, the breeding strategies have been proposed to develop maize ideotypes for silage for sustainable animal husbandry development.